(untitled) (JURNAL ADMINISTRASI PUBLIK, 2015)
In Indonesia increasingly important political advertising used by politicians in local elections and presidential elections, but also not free from controversy. Order to determine the effect of political advertising in the election of legislators in South Minahasa Regency Motoling more specifically in the district west. This type of research is the use of qualitative research, which is a type of research that is used to examine the object in which the researcher is as. the number of respondents who becomes the object of study is 50 people The results showed political advertising in the legislative elections have considerable influence, in plain view of political advertising is a political force in communicating with the people who became the object of political advertising. Keywords: Advertising Politics, Legislative Elections